FISHERIES SATISFACTION LEVEL OF PAYMENT ADDITIONAL SERVICES IN BUNGUS SAMUDERA FISHERIES PORT - Nia Kurnia; Syaifuddin Syaifuddin; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractOne form of service that has an important role in the world of fisheries is service in fishing ports. Providing services will affect the level of satisfaction of fishermen. Fisherman satisfaction is important in supporting the performance and development of a port. This study aims to determine the level of satisfaction of fishermen on anchoring services. This research was conducted at the Ocean Bungus Fishery Port. This research was conducted in April 2019 for 14 days. The method used is the survey method. Data analysis using the Customer Satisfaction Index (CSI), and Importance and Performance Analysis (IPA) using 10 assessment attributes.The results showed that there were 8 service attributes that were considered to have fulfilled fishermen's satisfaction, namely the existence of recipients of complaints, speed of repair of facilities, skills of service personnel, ease of ordering procedures, appearance of officers, set prices, cleanliness conditions, and security conditions. There are 1 service attribute that fishermen consider less important. Overall, fishermen are very satisfied with the anchoring services provided by the port. Keywords: Fisherman satisfaction level, PPS Bungus, Service